From Farm to Fork: Crickets as Alternative Source of Protein, Minerals, and Vitamins - Murugu, Dorothy K.; Onyango, Arnold N.; Ndiritu, Alex K.; Osuga, Isaac M.; Xavier, Cheseto; Nakimbugwe, Dorothy; Tanga, Chrysantus M. (Frontiers in Nutrition, 2021)
Globally, there is growing interest to integrate cricket-based ingredients (flour) into food products to combat food and nutrition insecurity. However, there is lack of information on in-depth nutrient profile of the two cricket species (Scapsipedus icipe and Gyrllus bimaculutus), which are the most widely consumed in Africa. Here we determined the nutrient composition of two cricket species and compared them with published records of key animal and plant sources. Our results revealed that the crude protein contents of S. icipe and G. bimaculatus were similar (56.8 and 56.9%, respectively) and comparable to those of animal protein sources. Both cricket species had balanced amino acid profiles that are superior to that of animal and plant sources, except for histidine and cysteine. The protein digestibility of S. icipe and G. bimaculatus ranged between 80 - 88%, which is comparable to that of common plant foods but slightly lower than that of animal proteins. The iron, Zinc and potassium contents were considerably higher in both cricket species compared to that of plant and animal sources. The calcium contents of both crickets (S. icipe and G. bimaculatus) was superior to that of plant and animal origin except for kidney beans and eggs, respectively. Riboflavin, thiamine, and folic acid concentrations of S. icipe and G. bimaculatus were superior to that of the conventional sources. Vitamin A levels were significantly higher in S. icipe compared to G. bimaculatus. This implies that S. icipe and G. bimaculatus can adequately contribute to our daily required nutrient intake. Thus, integrating cricket flours into ready-to-eat food products would address some of the most pressing nutritional deficiency challenges that many developing countries have to grapple with, particularly high risk to serious health problems such as anaemia, poor pregnancy outcomes, hypertension, increased risk of morbidity and mortality, stunted growth and impaired physical and cognitive development. We conclude that edible crickets present unique opportunities for improving food and nutritional insecurity status of both resource-poor and Western populations.